2004
DOI: 10.1177/039463200401700106
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Tumor-Associated Macrophages by Thymosin Alpha-1

Abstract: It was shown earlier that the progressive growth of a transplantable T-cell lymphoma of spontaneous origin, designated as Dalton's lymphoma (DL), in a murine host is associated with an inhibition of macrophages (TAM) along with an involution of thymus. However, it remained unclear if a decline in the level of thymic peptides in DL-bearing host, due to thymic regression, has any implications in the inhibited responses of TAM. Therefore, the present investigation was under taken to study whether the TAM of DL-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 29 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…This effect was associated with a significant augmentation in the number of circulating polymorphonuclear cells (PMNs) and of their candidacidal activity, although the issue of whether the effect of Tα1 on PMNs was a direct one on PMN precursor cells or mediated by other cell populations, such as lymphocytes or monocytes, remained unresolved at that time [21]. Studies by other groups of investigators also focused on the protective activity of Tα1 against opportunistic infections in animal models [22] and, more generally, on the capacity of Tα1 to potentiate several murine as well as human macrophage abilities [23,24,25]. Tα1 is able to upregulate the expression of the major histocompatibility complex class I in murine and human tumor cell lines and in primary cultures of human monocyte-enriched peripheral blood mononuclear cells (PBMCs) [26].…”
Section: Introductionmentioning
confidence: 99%
“…This effect was associated with a significant augmentation in the number of circulating polymorphonuclear cells (PMNs) and of their candidacidal activity, although the issue of whether the effect of Tα1 on PMNs was a direct one on PMN precursor cells or mediated by other cell populations, such as lymphocytes or monocytes, remained unresolved at that time [21]. Studies by other groups of investigators also focused on the protective activity of Tα1 against opportunistic infections in animal models [22] and, more generally, on the capacity of Tα1 to potentiate several murine as well as human macrophage abilities [23,24,25]. Tα1 is able to upregulate the expression of the major histocompatibility complex class I in murine and human tumor cell lines and in primary cultures of human monocyte-enriched peripheral blood mononuclear cells (PBMCs) [26].…”
Section: Introductionmentioning
confidence: 99%
“…Phagocytic activity of TAM was carried out as described earlier [22]. TAM grown on glass coverslips were incubated with heatkilled yeast cells (2 × 10 8 /ml) for 90 min at 37 • C in a CO 2 incubator.…”
Section: Assay Of Phagocytic Activitymentioning
confidence: 99%
“…As hematological malignancies are considered as one of the most complicated malignancies for clinical management [16,17], we have been studying various aspects of host-tumor relationship in a murine model of a transplantable T cell lymphoma of spontaneous origin designated as Dalton's lymphoma (DL) [18][19][20][21][22][23][24][25]. We have also shown that TAM of a DL-bearing host are in a suppressed state and resistant to signals of activation [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…NO released from activated macrophages suppressed the proliferation of tumor cells [12]. Coculture of macrophages and tumor cells leads to increased production of NO by the macrophages with concomitant cytotoxicity against the tumor cells [13]. TGF-␤1, suppresses the production of both superoxide [14] and NO by IFN-␥-induced macrophages [15].…”
Section: Introductionmentioning
confidence: 99%